The Effectiveness of Ullman's Dream Interpretation Group Sessions on Exploratory, Action, and Experiential Insights in Healthy Women - Fahimeh Askari; Iran Davoudi; AbdolKazem Neysi; Yadullah Zargar (پژوهش‌های کاربردی روانشناختی, 2022)
The purpose of this study is to examine the effect of an intervention program of dream interpretation group sessions using the Ullman method on exploratory, action, and experiential insights in healthy women. This is an applied and quasi-experimental study with a pretest/posttest and a control group. The population includes all Persian-speaking women living in Iran, aged 20 to 45 years, with at least a diploma, and able to access and work with the Internet in 2020, who were eligible to participate in the study based on the inclusion criteria. After publishing the invitation on the websites and virtual advertising pages of various cities, 20 people from this population were purposively selected (based on the inclusion criteria) and then randomly assigned to two experimental and control groups (10 people in each group). Data collection instruments were the Gains from Dream Interpretation (GDI) questionnaire and the intervention program, including the Ullmann's Appreciating Dreams Protocol (UADP), conducted online in 11 sessions of 90 to 120 minutes. Data were analyzed using multivariate analysis of covariance in SPSS-24 software. The results showed that the intervention program of group interpretation of dreams according to the Ullmann's method had a significant effect on exploratory and action insight (p < 0.05), but was not significant on experimental insight. Therefore, the Ullmann's Appreciating Dreams Protocol can be used to promote insight in the non-clinical population.